Daur Ulang Cell Tube X - Ray Analyzer dengan Membuat Alat Pemisah Cell Tube di Laboratorium PT Pertamina (Persero) RU III Plaju - Palembang - Nedia Sandika; Puspa Ratu; Djoko Suprapto (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2020)
Laboratory production Analyst & Gas section in Refinery Unit III, Laboratory production analyses of samples water, gas, chemicals, scale, waste water and oil analysis samples are chemicals, which are derived from the refinery and its surrounding environment. In the analysis of the example of oil, one of the parameters of its analysis is the SULFUR CONTENT. Analysis of the sulfur content is done using instruments, namely x-ray SULFUR ANALYZER, X-ray sulfur analyzer to operate using this Cell Tube as a sample container will be analyzed. During this analysis is completed, cell Tube disposed of along with its contents to the shelter of the waste materials are toxic and dangerous. This can hinder the process of lifting, loading and unloading and distributing fuel to various corners of the other areas. Because the certificate of its quality controlcould not be made because there is one very important reply analysis specified fuel products i.e. analysis of sulfur content could not be analyzed. If supplies cell tube is exhausted due to increased demand for analysis of sulfur and quite significant. By using simple tools and using the principle of the lever, the eventual cell tube former can split and cleaned so that it can be reused